2019
DOI: 10.1177/1367493518814926
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ standpoints on end-of-life decisions at the neonatal intensive care units in Jordan

Abstract: The purpose of this cross-sectional descriptive study is to explore pediatricians’ and neonatologists’ attitudes and standpoints on end-of-life (EOL) decision-making in neonates. Seventy-five physicians, employed fulltime to care for newborns in 23 hospitals in Jordan, completed internationally accepted questionnaires. Most physicians (75%) were supportive of using life-sustaining interventions, irrespective of the severity of the newborns’ prognosis and the potential burden of the neonates’ disabilities on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…In other studies, Guimarães et al [38] and Abdel Razeq [35] for example, additional factors predictive of physicians' practices have been identified; prominent among them are cultural and religious factors. Although religion was not revealed as a statistically significant variable predicting physicians' decision-making when faced with ethical dilemmas in neonatal intensive care, its relevance cannot be ignored in the context of the present study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In other studies, Guimarães et al [38] and Abdel Razeq [35] for example, additional factors predictive of physicians' practices have been identified; prominent among them are cultural and religious factors. Although religion was not revealed as a statistically significant variable predicting physicians' decision-making when faced with ethical dilemmas in neonatal intensive care, its relevance cannot be ignored in the context of the present study.…”
Section: Discussionmentioning
confidence: 92%
“…International studies have shown that the attitude and practices of healthcare professionals regarding ethical decision-making in intensive neonatal care differs significantly depending on the specific legal, economic, religious, historical, and general cultural conditions and characteristics of each country [35][36][37][38]. Country of origin emerges as the main differentiation factor of clinical behaviors pertaining to neonatal intensive care [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that country of origin, cultural background and religious background influence physicians' attitudes and practice of medicine, including EOL care, although only in relatively few studies [6,7]. Some previous studies have shown that Muslim physicians are more likely than non-Muslim physicians to object to the concepts of withdrawal from life support or artificial nutrition, physician-assisted suicide, and terminal sedation [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Around 62%-93% of NICU deaths worldwide follow EoLDs as to withhold and primarily to withdraw treatment, thus affecting infant mortality. [12][13][14][15] Consequently, EoLDs should be considered in the evaluation of NICUs' treatment outcomes, as for survival in respect to the NICU's morbidity rate. 16 Recent literature provides valuable data on physicians' opinions, attitudes and end of life practices, particularly regarding long term morbidity of extremely premature infants.…”
Section: Introductionmentioning
confidence: 99%